2021
DOI: 10.1177/03000605211016274
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune-inflammation index as a promising predictor of mortality in patients with acute coronary syndrome: a real-world study

Abstract: Objective Prognostic indicators in acute coronary syndrome (ACS) would aid in decision-making and identifying high-risk patients. The systemic immune-inflammation index (SII) has good prognostic value in many diseases; however, its use has not been reported for ACS. We aimed to determine the associations between the SII and outcomes in patients with ACS, with adjustment for confounders. Methods In this retrospective cohort study, we used the MIMIC-III (Multiparameter Intelligent Monitoring in Intensive Care) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…(9)(10)(11)(12) In a study conducted in patients with the acute coronary syndrome, they investigated the comorbidities of the patients using the Elixhauser Comorbidity Index and it was found that the SII value was higher in patients with comorbidity. (13) To the best of our knowledge, the usefulness of the SII was evaluated for the first time for upper GI bleeding in the present study; however, it was not a useful parameter in predicting the Forrest classification as well as in determining the likelihood of bleeding present during esophagoduednoendoscopy.…”
Section: Discussionmentioning
confidence: 69%
“…(9)(10)(11)(12) In a study conducted in patients with the acute coronary syndrome, they investigated the comorbidities of the patients using the Elixhauser Comorbidity Index and it was found that the SII value was higher in patients with comorbidity. (13) To the best of our knowledge, the usefulness of the SII was evaluated for the first time for upper GI bleeding in the present study; however, it was not a useful parameter in predicting the Forrest classification as well as in determining the likelihood of bleeding present during esophagoduednoendoscopy.…”
Section: Discussionmentioning
confidence: 69%
“…10,11 On the other hand, several studies have reported the prognostic value of high SII for acute coronary artery disease and type B aortic dissection. [12][13][14] And our study further related preoperative systemic inflammation with prognosis of ATAD underwent surgery. The results showed that SII is an independent biomarker of short-term outcomes in patients with ATAD surgery.…”
Section: Discussionmentioning
confidence: 72%
“…The SII is an indicator composed of platelet, neutrophil, and lymphocyte counts, whose formula is: platelet counts × neutrophil counts/lymphocyte counts. It has shown possible prognostic prediction abilities in malignant tumors, coronary artery disease, and acute IS [ 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%